2020
DOI: 10.1103/physrevb.101.125121
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced anomalous Hall effect in the magnetic topological semimetal Co3Sn2xInxS2

Abstract: We study the anomalous Hall effect (AHE) of single-crystalline Co 3 Sn 2−x In x S 2 over a large range of indium concentration x from 0 to 1. Their magnetization reduces progressively with increasing x while their ground state evolves from a ferromagnetic Weyl semimetal into a nonmagnetic insulator. Remarkably, after systematically scaling the AHE, we find that their intrinsic anomalous Hall conductivity (AHC) features an unexpected maximum at around x = 0.15. The change of the intrinsic AHC corresponds with t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 44 publications
8
41
0
Order By: Relevance
“…4c). Last, we observe In dopant in the vacancy surface in the main paper, and In is known to substitute the Sn atom both experimentally and theoretically [20][21][22] .…”
Section: Methodsmentioning
confidence: 64%
See 2 more Smart Citations
“…4c). Last, we observe In dopant in the vacancy surface in the main paper, and In is known to substitute the Sn atom both experimentally and theoretically [20][21][22] .…”
Section: Methodsmentioning
confidence: 64%
“…We further conclude this assignation by doping the bulk Co 3 Sn 2 S 2 single crystals with 1% In impurities and imaging the layerselective In-dopants. The In impurities preferentially replace the Sn atoms according to previous experimental and theoretical studies 20,21 , as well as our recent systematic single-crystal growth 22 . Indeed, on the vacancy surface identified 11 to be Sn, we observe dilute substitutional atoms with consistent concentration ( Fig.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…At the same time, a large Berry curvature associated with the SOC-gapped Weyl lines was found at the Fermi level in calculations, while the predicted AHE exhibited its maximum value very close to the Fermi level and dropped steeply as one approached the Weyl point energy [180]. As a result, some works suggested that the large AHE and ANE arise predominantly due to Berry curvature concentrated by the Weyl lines [185][186][187]. More broadly, Co 3 Sn 2 S 2 has been a rich playground for a variety of phenomena bringing together the kagome lattice, magnetism and topology, such as negative flat-band magnetism [188].…”
Section: Topological Nodal Line Semimetalsmentioning
confidence: 87%
“…Given the structural and magnetic stabilities, we propose Co-Pb-S and Co-SnPb-S as magnetic shandite compounds that may be synthesized by experiments. Interestingly, recently, the alloy system Co 3 Sn 2 -xInxS 2 has been synthesized 40,41 by the Bridgeman technique 42 and was identified to maintain a large AHC (1500 ± 300 Ω −1 cm −1 at x = 0.15). Our calculations also confirmed the stability of Co-Sn-S, as it has already been synthesized and identified as an FM WSM 43 .…”
Section: Crystal Structures and Magnetic Ground States For Co-mm'-xmentioning
confidence: 99%